Acute toxicological assessment of seashore mangosteen (Garcinia hombroniana) aqueous extract - Othman, Dyary Hiewa; Abdul Kadir, Arifah; Kumar Sharma, Reuben Sunil; Abdullah, Rasedee; Md. Sukari, Mohd Aspollah; Zakaria, Zainul Amiruddin; Ahmad, Zuraini; Abdullah, Muhammad Nazrul Hakim (Veterinary Association Malaysia, 2016)
Garcinia hombroniana has been used in Malay traditional medicine to treat various disorders such as abdominal pain and gonorrhea, and little is known about its toxicological properties. This study investigated the acute toxicological effects of the plant’s leaves aqueous extract using theoral acute toxic class (ATC) method. Twenty-four female Sprague-Dawley rats were divided into T1, T2, T3 and control groups. The T1, T2 and T3 rats administered a single oral dose of 300, 2000 and 5000 mg/kg of G. hombroniana leaves aqueous extract, respectively. The animals were checked daily for abnormal clinical signs and mortality rate for 14 days. The body weight, daily food and water consumption were recorded. The haematological and biochemical parameters of blood as well as relative organ weight and tissues histology such as heart, kidney, liver and spleen were evaluated. Results have shown significantly decreased (p< 0.05) food and water consumption in T2 and T3 rats, which returned to normal after 72 hr post administration. No significant differences (p≥0.05) in the haematological and serum biochemical parameters in the treated rat groups, compared to the untreated control animals. An increase in the relative weight of spleen was noticed in T3 animals. Congestion of the splenic, hepatic, cardiac and renal tissues was seen in T2 and T3 rats. The oral LD50 was higher than 5000 mg/kg of body weight. Thus, it can be concluded that G. hombroniana aqueous extract shows little toxicity in the laboratory rats and the therapeutic potentials should be further investigated.